Solution focused brief therapy : 100 key points and techniques - Ratner, Harvey; George, Evan, 1951-; Iveson, Chris (London : Routledge/Taylor and Francis Group, 2012)
'Solution Focused Brief Therapy: 100 Key Points and Techniques provides a concise and jargon-free guide to the thinking and practice of this exciting approach, enabling people to make changes in their lives quickly and effectively. It covers: - This history and background to solution focused practice - The philosophical underpinnings of the approach - Dealing with difficult situations - Specific applications to children, adolescents, families , and schools - Organisational applications including supervision, coaching and leadership. - Frequently asked questions This book is an invaluable resource for all therapists and counsellors, whether in training or practice. It will also be essential for any professional whose job it is to help people make changes in their lives, and will therefore be of interest to social workers, probation officers, psychiatric staff, doctors, and teachers, as well as those working in organisations as coaches and managers'--
Includes references : p. 249-254.
Keywords: Solution-focused brief therapy